Unveiling the Determinants of Primary Consumer Goods Firms' Performance - Avenia Melani; Siti Nurlaela; Riana Rachmawati Dewi (Universitas Tidar, 2025)
The study's goal is to unveil the factors affecting financial performance, including liquidity, leverage, firm size, environmental impact, and capital structure. Consumer goods sector companies listed between 2021 and 2023 on PROPER and the Indonesia Stock Exchange served as research samples. Purposive sampling is then used to choose multiple samples that satisfy specific requirements, leaving 29 businesses. Multiple linear regression was used to examine the samples using SPSS version 25. The research results give stakeholders the impression that leverage has a positive effect on financial performance, while company size has a negative effect on financial performance. However, financial performance is unaffected by liquidity, environmental performance, and capital structure. Signaling theory explains how primary consumer goods companies provide financial information and business strategies to reduce information asymmetry and influence market perceptions.